Adaptive Version Clocks and the OffSync Protocol - Neumann, Christoph; Wahl, Andreas Maximilian; Lenz, Richard (Proc of the 10th IEEE Int'l Symposium on Parallel and Distributed Processing with Applications (ISPA-12, 2012)
The alpha-OffSync project offers a synchronization concept for alpha-Flow, an electronic process support in heterogeneous inter-institutional scenarios in healthcare. A distributed case file is provided by alpha-Flow to represent workflow schemas as documents which are shared coequally to content documents. alpha-OffSync allows the detection and resolution of global concurrent modification conflicts on process artifacts based on locally available information by using logical timestamps. Further mechanisms are included to ease the management and dynamic extension of the group of participating actors. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD6.adapti
Keywords: ProMed; alpha-Flow

A Light-Weight System Extension Supporting Document-based Processes in Healthcare - Neumann, Christoph; Lenz, Richard (Proceedings of the 3rd Int'l Workshop on Process-oriented Information Systems in Healthcare in conjunction with the 7th Int'l Conf on Business Process Management, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.alight
Keywords: ProMed

alpha-Adaptive: Evolutionary Workflow Metadata in Distributed Document-Oriented Process Management - Neumann, Christoph; Wahl, Andreas Maximilian; Lenz, Richard; Schwab, Peter (Proc of the 4th Int'l Workshop on Process-oriented Information Systems in Healthcare (ProHealth'11) in conjunction with the 9th Int'l Conf on Business Process Management (BPM'11), 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.alphaa

alpha-Flow: A Document-based Approach to Inter-Institutional Process Support in Healthcare - Neumann, Christoph; Lenz, Richard (Proceedings of the 3rd Int'l Workshop on Process-oriented Information Systems in Healthcare in conjunction with the 7th Int'l Conf on Business Process Management, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.alphaf
Keywords: ProMed; alpha-Flow

alpha-OffSync: An Offline-Capable Synchronization Approach for Distributed Document-Oriented Process Management in Healthcare - Wahl, Andreas Maximilian; Neumann, Christoph (Lecture Notes in Informatics (LNI) Seminars 11 / Informatiktage 2012, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD6.alphao
Keywords: ProMed; alpha-Flow

A Mediated Publish-Subscribe System for Inter-Institutional Process Support in Healthcare - Neumann, Christoph; Daum, Michael; Lenz, Richard; Rampp, Florian (Proceedings of the 3rd ACM Int'l Conf on Distributed Event-Based Systems, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.amedia
Keywords: ProMed; DEUS

DEUS: Distributed Electronic Patient File Update System - Neumann, Christoph; Lenz, Richard; Rampp, Florian (2012)
UnivIS-Import:2016-06-30:Pub.2012.tech.IMMD.IMMD6.deusdi

Distributed Ad Hoc Cooperation in Healthcare - Neumann, Christoph; Lenz, Richard (Process Support and Knowledge Representation in Healthcare, 2013)
Inter-institutional cooperation among physicians becomes increasingly important. Yet, it is unrealistic to assume that cooperation can be supported via a homogeneous system that is pre-installed in every organization. Instead, physicians will typically have their own autonomous systems that support internal processes. Traditional activity-oriented workflow platforms do not resolve inter-institutional integration challenges. This paper presents an approach for distributed process management, which enables ad hoc cooperation via active electronic documents without the need to integrate local systems. A distributed case file is used to coordinate cooperating parties. Using this case file does not require any preinstalled system components, so genuine ad hoc information exchange is enabled. © Springer-Verlag 2013.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD6.distri

Exploitation of Event-Semantics for Distributed Publish/Subscribe Systems in Massively Multiuser Virtual Environments. - Fischer, Thomas; Daum, Michael; Irmert, Florian; Neumann, Christoph; Lenz, Richard (In Proceedings of the 2010 international Symposium on Database Engineering & Applications, 2010)
Triggered by the fast evolving technical capabilities for implementing distributed global scale applications, online games have grown to a huge industry in recent years. Particularly, Massive Multiuser Virtual Environments (MMVEs), which allow for simultaneous activity of thousands of players in a virtual world, have been tremendously successful. Current architectures, however, use centralized approaches, which obviously do not scale beyond a certain point. Distributed event-based systems are a promising approach to reach both, performing and scalable architectures. The potential of this approach can only be fully exploited if event semantics is used to optimize event handling. Existing approaches actually do this to some degree, but typically in a very application specific manner. There is no generally applicable framework for classifying events according to their relevant semantic properties. In this paper, we propose a generally applicable classification of events as a first step on the way to exibly adaptable generic event management systems. We exemplify the relevance of our semantic properties by classifying typical events in an existing MMVE. We discuss existing optimization strategies based on our semantic classification and outline a corresponding architecture. Copyright 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.exploi

Hydra Version Control System - Neumann, Christoph; Lenz, Richard; Hady, Scott (Proc of the 10th IEEE Int'l Symposium on Parallel and Distributed Processing with Applications (ISPA-12, 2012)
The Hydra project offers version control for distributed case files in alpha-Flow. Available version control systems lack support for independent versioning of multiple logical units within a single repository each with its own version history and head. Our use case also requires mechanisms for labeling versions by their validity and for validity-based navigational access. Hydra is a multi-module and validity-aware version control system. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD6.hydrav
Keywords: ProMed; alpha-Flow

Integration verteilter und heterogener Configuration-Management-Datenbanken - Blechinger, Juliane; Neumann, Christoph; Lenz, Richard; von Jouanne-Diedrich, Holger; Schwarz, Stefan (Informatik-Spektrum, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.IMMD.IMMD6.integr_6

OXDBS Erweiterung einer nativen XML-Datenbank um die Validierung und Konsistenzprüfung gegen eine OWL-Ontologie - Neumann, Christoph; Lenz, Richard; Hanisch, Stefan; Schiemann, Bernhard (Tagungsband, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.oxdbse
Keywords: ProMed

OXDBS – Extension of a native XML Database System with Validation by Consistency Checking of OWL-DL Ontologies - Neumann, Christoph; Fischer, Thomas; Lenz, Richard (Proc of the 14th International Database Engineering & Applications Symposium, 2010)
Native XML database systems provide mature technology for persisting XML data and documents. Ontologies are often represented as XML-based documents like OWL-DL ontologies which allow for semantic consistency checking by formal description logic. Artificial intelligence provides reasoners as IT-support for consistency checking. Currently there exists no native XML database system which integrates logic reasoning for semantic consistency as addition to syntactic schema validation. The OXDBS project integrates a reasoner into a native XML database system, thus, allowing to assert consistency of ontological data at the most basic tier in an application environment. Copyright © 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.oxdbse
Keywords: ProMed

OXDBS - Extension of a native XML Database System with Validation by Consistency Checking of OWL-DL Ontologies - Neumann, Christoph; Fischer, Thomas; Lenz, Richard (2010)
Native XML database systems provide mature technology for persisting XML data and documents. Ontologies are often represented as XML-based documents like OWL-DL ontologies which allow for semantic consistency checking by formal description logic. Artificial intelligence provides reasoners as IT-support for consistency checking. Currently there exists no native XML database system which integrates logic reasoning for semantic consistency as addition to syntactic schema validation. The OXDBS project integrates a reasoner into a native XML database system, thus, allowing to assert consistency of ontological data at the most basic tier in an application environment.
Keywords: Semantic Web and Databases; Logic and Databases; Medical Systems; Data Quality and Semantics

Semantics of a Runtime Adaptable Transaction Manager - Irmert, Florian; Lauterwald, Frank; Neumann, Christoph; Daum, Michael; Lenz, Richard; Meyer-Wegener, Klaus (Proceedings of the International Database Engineering and Applications Symposium, 2009)
Database Management Systems (DBMSs) that can be tailored to specific requirements offer the potential to improve reliability and maintainability and simultaneously the ability to reduce the footprint of the code base. If the requirements of an application change during runtime the DBMS should be adapted without a shutdown. Runtime-adaptation is a new and promising research direction to dynamically change the behavior of a DBMS. Especially the adaptation of the Transaction Manager (TM) states a challenge. In this paper, we present the session semantics of a runtime-adaptable TM. We define preliminaries and assumptions to activate the TM during sessions from a conceptual point of view. The advantages and disadvanteges of different approaches are discussed, especially regarding the occurence of ANSI SQL phenomena. From a technical point of view, we define requirements for the architecture of the TM and the DBMS that arose in our prototype. Copyright ©2009 ACM.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.semant
Keywords: Adaptation; Runtime; SQL phenomena; Transaction management

Technische Grundlagen für eine laufzeitadaptierbare Transaktionsverwaltung - Irmert, Florian; Neumann, Christoph; Daum, Michael; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Datenbanksysteme in Business, Technologie und Web (BTW), 2009)
Auf spezielle Anwendungen zugeschnitte Datenbankverwaltungssysteme (DBMS) erfordern in den meisten Fällen Individuallösungen, welche einen erhöhten Entwicklungs- und Wartungsaufwand mit sich bringen. Es fehlen modulare DBMS-Architekturen als konfigurierbare Standardlösung, die beliebig schlanke als auch umfangreiche Architekturen ermöglichen. Die Transaktionsverwaltung als querschneidender Belang durchdringt in herkömmlichen DBMS die Architektur und verhindert die Modularisierung. In dieser Arbeit wird die Transaktionsverwaltung aus einem DBMS herausgelöst und durch eine eigenständige, wiederverwendbare Komponente realisiert. Die Architektur der gekapselten und wiederverwendbaren Transaktionsverwaltung wird dokumentiert, sowie die aspektorientierte Verknüpfung zwischen reduziertem DBMS und separater Transaktionsverwaltung beschrieben. Als Grundvoraussetzung für zukünftige, sich selbstverwaltende DBMS kann die Transaktionsverwaltung zur Laufzeit dynamisch hinzugefügt und entfernt werden. Die prototypische Implementierung wird an Hand von SimpleDB in Verbindung mit einem dynamischen AOP Framework erläutert.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.techni
Keywords: data base management systems; transactions; modularization; cross-cutting concerns; dynamic aspect oriented programming; AOP; CoBRA DB

The Alpha-Flow Approach to Inter-Institutional Process Support in Healthcare - Neumann, Christoph; Lenz, Richard (International Journal of Knowledge-Based Organizations, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.IMMD.IMMD6.thealp

The alpha-Flow Use-Case of Breast Cancer Treatment - Modeling Inter-Institutional Healthcare Workflows by Active Documents - Neumann, Christoph; Lenz, Richard (2010)
In healthcare, inter-institutional process support implicates decentralized and ad-hoc workflows. From the perspective of system integration, the autonomy of the sites which are participating in a healthcare network is mostly untouchable. Traditional activity-oriented workflow models or content-oriented workflow models do not provide adequate support in such system environments and workflow scenarios. The objective of the alpha-Flow approach is to enable distributed, ad-hoc process support with initially unknown sets of actors and institutions. In its document-oriented workflow model, electronic documents become active documents and act as software agents as the primary means of coordination. This paper details the healthcare use-case for the alpha-Flow model by the example of cooperative breast-cancer treatment scenarios.
Keywords: Healthcare; information systems; document-orientation; inter-institutional; dynamic collaborations

The alpha-Flow Use-Case of Breast Cancer Treatment – Modeling Inter-Institutional Healthcare Workflows by Active Documents - Neumann, Christoph; Lenz, Richard (Proc of the 8th Int'l Workshop on Agent-based Computing for Enterprise Collaboration, 2010)
In healthcare, inter-institutional process support implicates decentralized and ad-hoc workflows. From the perspective of system integration, the autonomy of the sites which are participating in a healthcare network is mostly untouchable. Traditional activity-oriented workflow models or content-oriented workflow models do not provide adequate support in such system environments and workflow scenarios. The objective of the alpha-Flow approach is to enable distributed, ad-hoc process support with initially unknown sets of actors and institutions. In its document-oriented workflow model, electronic documents become active documents and act as software agents as the primary means of coordination. This paper details the healthcare use-case for the alpha-Flow model by the example of cooperative breast-cancer treatment scenarios. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.thealp
Keywords: ProMed; alpha-Flow

The Erlangen Glaucoma Registry: a Scientific Database for Longitudinal Analysis of Glaucoma - Lauterwald, Frank; Neumann, Christoph; Lenz, Richard; Jünemann, Anselm; Mardin, Christian Y.; Meyer-Wegener, Klaus; Horn, Folkert (2011)
UnivIS-Import:2017-12-18:Pub.2011.tech.IMMD.IMMD6.theerl
Keywords: Glaukom; Elektronische Patientenakte; Register; Längsschnittuntersuchung; Wissenschaftliche Datenbank; Relationale Datenbank

XdsRig Eine Open-Source IHE XDS Testumgebung - Neumann, Christoph; Lenz, Richard; Wagner, Florian (Tagungsband, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.xdsrig
Keywords: ProMed